Measuring users' satisfaction with Malaysia's electronic government systems - Mohamed, Norshidah; Hussin, Husnayati; Hussein, Ramlah (Academic Conferences Ltd., 2009)
The research seeks to measure users' satisfaction and identify the contributors of satisfaction. We used the end-user computing satisfaction (EUCS) model as the a priori model to measure internal end-users' satisfaction with Malaysia's electronic government systems. We gathered data from internal end-users at the level of officers and directors of Malaysia's electronic government systems. Using the structural equation modeling approach, our results show that all five first-order factors, content, accuracy, timeliness, format and ease of use, explain the contributors of satisfaction. Further, our studies provide the evidence that in Malaysia's electronic government context, end-users' satisfaction priorities are timeliness, content and accuracy. This paper makes a significant contribution by applying the Information Systems body of knowledge to measure users' satisfaction with Malaysia's electronic government systems, test and validate the EUCS model in the context of Malaysia's electronic government environment. The paper has enhanced our understanding of users' demands for interactions with business, citizens and other government personnel in the Malaysian electronic government environment.